Floral biology and genetic marker for sex determination in canarium odontophyllum miq. (Dabai) - Ting, Jen Ching (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Dabai (a.k.a. Canarium odontophyllum) being a Sarawak's specialty fruit is well-known with its unique sexual characteristic. The hermaphrodite dabai trees bear fruits while male dabai trees do not and are normally removed when the plants are reproductively mature. Failure to determine gender at early stage can results in undesirable waste of breeding cost, which reflects a need for a rapid and consistent assay for sex identification. With the advent of molecuh,u marker, sex determination in plant is made possible by various marker applications! This research project outlined the utilization of random amplified polymorphic DNA (RAPD); sequence characterized amplified regions (SCAR); single nucleotide polymorphisms (SNP) and cleaved amplified polymorphic sequences (CAPS) for sex determination in dabai. A set of 64 RAPD markers were amplified by using the Bulk Segregant Analysis (BSA) approach and one RAPD marker was found to generate unique band in hermaphrodite samples (DH272). Cloned and sequenced DH272 was then converted into SCAR marker and tested for its polymorphism. Test results revealed that the SCAR marker amplified single product, but did not differentiate between the two sextypes upon Polymerase Chain Reaction (PCR) amplification. In order to recover its polymorphism, sequence information of two male-specific and one hermaphrodite-specific SCAR products were subjected to SNP discovery and subsequently CAPS identification. Five SNPs were detected and one CAPS site, TaqI which is located with T-G base substitution on the recognition sequence was identified. It is of high possibility that the CAPS marker would discriminate hermaphrodite from male plants via PCR amplification and further restricted with the restriction endonuclease. Although more sample sequences are in need for additional SNP discovery, this assay coupling RAPD, SCAR, SNP and CAPS is believed to have bring success for sex determination in dabai and in short time, estabHsh a Dabai Sex Typing System (DSTS) for sex detection of dabai at the seedling stage. Utility of this diagnostic assay has a great potential in facilitating dabai improvement and conservation programmes and thereby in advance, proposing an economic and yet profitable planting approach for dabai plantation. In this project, floral morphological study of Canarium odontophyllum was also documented to further elucidate the molecular findings.